The effect of age in breast conserving therapy: A retrospective analysis on pathology and clinical outcome data. Issue 3 (March 2015) - Chen, Wei; Sonke, Jan-Jakob; Stroom, Joep; Bartelink, Harry; Verheij, Marcel; Gilhuijs, Kenneth
Abstract Background and propose Age is an important prognostic marker of patient outcome after breast conserving therapy; however, it is not clear how age affects the outcome. This study aimed to explore the relationship between age with the cell quantity and the radiosensitivity of microscopic disease (MSD) in relation to treatment outcome. Materials and methods We employed a treatment simulation framework which contains mathematic models for describing the load and spread of MSD based on a retrospective cohort of breast pathology specimens, a surgery simulation model for estimating the remaining MSD quantity and a tumor control probability model for predicting the risk of local recurrence following radiotherapy. Results The average MSD cell quantities around the primary tumor in younger (age ⩽ 50 years) and older patients were estimated at 1.9 ∗ 108 cells and 8.4 ∗ 107 cells, respectively (P < 0.01). Following surgical simulation, these numbers decreased to 2.0 ∗ 107 cells and 1.3 ∗ 107 cells (P < 0.01). Younger patients had smaller average surgical resection volume (118.9 cm3) than older patients (162.9 cm3, P < 0.01) but larger estimated radiosensitivity of MSD cells (0.111 Gy−1 versus 0.071 Gy−1, P < 0.01). Conclusion The higher local recurrence rate in younger patients could be explained by larger clonogenic microscopic disease cell quantity, even though the microscopic disease cells were found to be more radiosensitive.